Anaphylatoxins orchestrate Th17 response via interactions between CD16+ monocytes and pleural mesothelial cells in tuberculous pleural effusion. - Shuanglinzi Deng; Xinyue Hu; Lisha Luo; Wei Tang; Yuanyuan Jiang; Feifei Yin; Chengping Hu; Juntao Feng; Xiaozhao Li (Public Library of Science (PLoS), 2021)
The complement system is activated in tuberculous pleural effusion (TPE), with increased levels of the anaphylatoxins stimulating pleural mesothelial cells (PMCs) to secrete chemokines, which recruit nonclassical monocytes to the pleural cavity. The differentiation and recruitment of naive CD4+ T cells are induced by pleural cytokines and PMC-produced chemokines in TPE. However, it is unclear whether anaphylatoxins orchestrate CD4+ T cell response via interactions between PMCs and monocytes in TPE. In this study, CD16+ and CD16- monocytes isolated from TPE patients were cocultured with PMCs pretreated with anaphylatoxins. After removing the PMCs, the conditioned monocytes were cocultured with CD4+ T cells. The levels of the cytokines were measured in PMCs and monocyte subsets treated separately with anaphylatoxins. The costimulatory molecules were assessed in conditioned monocyte subsets. Furthermore, CD4+ T cell response was evaluated in different coculture systems. The results indicated that anaphylatoxins induced PMCs and CD16+ monocytes to secrete abundant cytokines capable of only inducing Th17 expansion, but Th1 was feeble. In addition, costimulatory molecules were more highly expressed in CD16+ than in CD16- monocytes isolated from TPE. The interactions between monocytes and PMCs enhanced the ability of PMCs and monocytes to produce cytokines and that of monocytes to express HLA-DR, CD40, CD80 and CD86, which synergistically induced Th17 expansion. In the above process, anaphylatoxins enhanced the interactions between monocytes and PMCs by increasing the level of the cytokines IL-1β, IL-6, IL-23 and upregulating the phenotype of CD40 and CD80 in CD16+ monocytes. Collectively, these data indicate that anaphylatoxins play a central role in orchestrating Th17 response mainly via interactions between CD16+ monocytes and PMCs in TPE.